Prevalence of oncology nurses' compassion satisfaction and compassion fatigue: Systematic review and meta‐analysis - Maaidah Algamdi (Wiley, 2022)
Abstract Aim To systematically review and comprehensively analyse findings of studies reporting oncology nurses' compassion satisfaction (CS), burnout (BO) and secondary traumatic stress (STS), measured by the professional quality of life (ProQOL) scale, and explore CS and CF related factors. Design Systematic review and meta‐analysis of cross‐sectional and interventional studies. Method Electronic databases were searched using keywords, and the review followed PRISMA guidelines. The prevalence of CS, BO and STS and their instrumental ratings were pooled using random effects meta‐analyses. Meta‐regression studies explored the effects of variables. Results Fifteen studies (sample size 2,509) were reviewed, and nine were in the meta‐analysis. The prevalence of CS, BO, and STS were 22.89%, 62.79% and 66.84%, respectively. No substantial correlation was found for independent variables, possibly due to sample size. There was a weak negative correlation between CS and BO [−0.06(0.90)] and a weak positive correlation between CS and STS [0.20(0.70)].